Economics of the public sector - Stiglitz, Joseph E. (New York : W.W.Norton Company, 2000)
Economics
Keywords: Public sector; Fiscal policy; Public expenditure; Public choice; Public productionCost-benefit analysis; Social insurance; Taxation; Tax incidence; Finance